Triple Valvulopathy and Jaccoud’s Arthropathy: A Case Report and Literature Review - Ali Naderi Mahabadi; Bassam Alhaddad; Stanley Ballou (Case Reports in Rheumatology)
Cardiac involvement is fairly common in patients with systemic lupus erythematosus (SLE). It may involve all layers of the heart and coronary arteries as well as the heart valves. We report an extremely rare presentation of valvulitis and valvular dysfunction associated with systemic lupus erythematosus. This is the first case of lupus valvulitis which required three mechanical prosthetic valve replacements with disease recurrence leading to a fatal outcome. This is, in our point of view, the consequence of aggressive natural history of the disease and perhaps late diagnosis and treatment of underlying SLE which was unsuccessful.